Technical Intraoperative Maneuvers for the Management of Inferior Vena Cava Thrombus in Renal Cell Carcinoma - Dellaportas, Dionysios; Arkadopoulos, Nikolaos; Tzanoglou, Ioannis; Bairamidis, Evgenios; Gemenetzis, George; Xanthakos, Pantelis; Nastos, Constantinos; Kostopanagiotou, Georgia; Vassiliou, Ioannis; Smyrniotis, Vassilios (Frontiers in Surgery, 2017)
Introduction: Renal vein or inferior vena cava (IVC) invasion by neoplastic thrombus in patients with renal cell carcinoma is not an obstacle for radical oncological treatment. The aim of this study is to present our technical maneuvers for complete removal of the intracaval thrombus without compromising hemodymanic stability of the patient. Materials and Methods: Between 2000 and 2014, 15 renal cell carcinoma patients with IVC involvement of levels I-III were treated with curative intent and were prospectively studied. The operative technique varied according to thrombus extent. For type I, extraction of the thrombus is facilitated by a 2-3cm longitudinal incision on the IVC that begins at the level of the renal vein and extends cranially, encompassing a vessel wall rim of the orifice of the resected renal vein. For type II cases the IVC is clamped above the neoplastic thrombus and for type III the IVC clamping is combined with hepatic blood flow control with ‘Pringle maneuver’. For type IV the IVC is clamped above the diaphragm, or if the thrombus extends into the right atrium cardiothoracic input is appropriate. Results: The main operative steps include preparation and control of the renal vessels and the IVC. Occasionally, for type III tumor thrombi the patient becomes hemodynamically unstable when IVC is clamped suprahepatically. In such a case, a novel operative maneuver of milking the thrombus below the orifice of the hepatic veins, and subsequently the IVC clamp also beneath the hepatic veins, allowing release of the ‘Pringle maneuver’ is performed. This operative step restores hepatic blood flow and hemodynamic stability, and is based on the floating nature of the thrombus into the IVC. Mean operative time was 120 minutes (range from 90 to 180 minutes), and average liver and renal warm ischemia time was 20 minutes (range from 15 to 35 minutes). Postoperative overall hospital stay ranged from 7 to 13 days. Conclusions: The technical solutions employed in the current study allow successful removal of neoplastic thrombi from the IVCin most cases, associated with minimal perioperative complication rate even for patients who-due to multiple comorbidities would be considered otherwise inoperable.